Símbolo e sabedoria prática Carl Gustav Jung e o mal-estar da modernidade - Marco Heleno Barreto (2006)
In this thesis, granting the recognizable philosophic dimension present in the field of contemporary psychotherapy, the author determines the nature of this dimension as analogous to phronesis or practical wisdom constitutive of philosophical life in the schools of Antiquity. In order to accomplish this goal, Carl Gustav Jungs Analytical Psychology is taken as the object of analysis, and it is demonstrated that in its practical dimension it can be adequately comprehended as a form of practical wisdom, namely as a living hermeneutics of symbolic images. Alongside with this demonstration, the historical, philosophical and cultural meaning of Analytical Psychology is shown to stem from its insertion in the experience of modernity, as a search for responses to the soul sufferings engendered by this same experience.